Peningkatan Inovasi Guru Melalui Kepemimpinan Transformasional Kepala Sekolah Dan Motivasi Berprestasi - Andi Supriyana; Bibin Rubini; Herfina Herfina (Universitas Pakuan, 2022)
Improving Teacher Innovation through Transformational Leadership of School Principles and Achievement MotivationThis study aims to formulate concrete efforts in order to improve teacher innovation through a study on the relationship between; 1) transformational leadership and teacher innovation, 2) achievement motivation and teacher innovation, 3) transformational leadership and achievement motivation together with teacher innovation. This research was carried out at a private junior high school in Bogor Tengah District, Bogor City. This study was taken in correlational research using a quantitative approach. The population in this study were all permanent teachers of the Bogor City Private Junior High School foundation; 165 of 15 private junior high schools. The research sample was 117 people taken by proportional random sampling technique. The results of the study at a significant level of 5% showed that: 1) transformational leadership had a positive effect on teacher innovation where the correlation coefficient was ry1 = 0.53 and transformational leadership contributed 27.8% to teacher innovation, 2) achievement motivation had a positive effect on innovation teachers where the correlation coefficient was ry2 = 0.24 and achievement motivation contributed 5.9% to teacher innovation, 3) transformational leadership and achievement motivation together with teacher innovation as indicated by the correlation coefficient ry12 = 0.54 and transformational leadership and achievement motivation simultaneously contributed 29.1% to teacher innovation. The conclusion is that the higher the level of transformational leadership and achievement motivation, the higher the innovation of the teacher.